Losing heart? The effect of job displacement on health - Sandra E. Black; Paul J. Devereux; Kjell G. Salvanes (Institute for the Study of Labor (IZA), 2012)
Job reallocation is considered to be a key characteristic of well-functioning labor markets, as more productive firms grow and less productive ones contract or close. However, despite its potential benefits for the economy, there are significant costs that are borne by displaced workers. We study how job displacement in Norway affects cardiovascular health using a sample of men and women who are predominantly aged in their early forties. To do so we merge survey data on health and health behaviors with register data on person and firm characteristics. We track the health of displaced and non-displaced workers from 5 years before to 7 years after displacement. We find that job displacement has a negative effect on the health of both men and women. Importantly, much of this effect is driven by an increase in smoking behavior. These results are robust to a variety of specification checks.
Keywords: I18; C14; J64; J65; 330; job loss; health; health behavior; Kündigung; Arbeitskräfte; Gesundheit; Schätzung; Norwegen